Corruption, fraud and internal control - IONESCU, Luminiţa (Annals of Spiru Haret University. Economic Series, 2010)
The economic crunch created a specific context for activity and profitability failing. The corruption is more and more common in our days. In the same time, the amount of money lost by businesses and the public sector to larger frauds increased last year to unthinkable limits. The shareholders expect the directors to take care to protect their company’s assets. This is why the financial controller has a very important role in each organization. The techniques to detect corruption or a fraud are developing every year. Thus, the introduction of computerized accounting has created the opportunities to conduct very comprehensive tests at relatively little cost. However, the fraudsters became more and more clever, and the controllers are responsible for the prevention and detection of fraud. The procedures that controllers should adopt with regard to fraud depend on the risk that fraud could occur and remain undetected and also the risk of that fraud impairing the truth and fairness of the statement.